First confirmed ultra-compact dwarf galaxy in the NGC 5044 group - Faifer, Favio Raúl (2017)
Context. Ultra-compact dwarfs (UCDs) are stellar systems displaying colours and metallicities between those of globular clusters (GCs) and early-type dwarf galaxies, as well as sizes of Reff 100 pc and luminosities in the range-13.5 < MV<-11 mag. Although their origin is still subject of debate, the most popular scenarios suggest that they are massive star clusters or the nuclei of tidally stripped dwarf galaxies. Aims. NGC 5044 is the central massive elliptical galaxy of the NGC 5044 group. Its GC/UCD system is completely unexplored. Methods. In Gemini+GMOS deep images of several fields around NGC 5044 and in spectroscopic multi-object data of one of these fields, we detected an unresolved source with g′ ∼ 20.6 mag, compatible with being an UCD. Its radial velocity was obtained with FXCOR and the penalized pixel-fitting (pPXF) code. To study its stellar population content, we measured the Lick/IDS indices and compared them with predictions of single stellar population models, and we used the full spectral fitting technique. Results. The spectroscopic analysis of the UCD revealed a radial velocity that agrees with the velocity of the elliptical galaxy NGC 5044. From the Lick/IDS indices, we have obtained a luminosity-weighted age and metallicity of 11.7+ 1.4 -1.2 Gyr and [Z/H] =-0.79 ± 0.04 dex, respectively, as well as [α/Fe] = 0.30 ± 0.06. From the full spectral fitting technique, we measured a lower age (8.52 Gyr) and a similar total metallicity ([Z/H] =-0.86 dex). Conclusions. Our results indicate that NGC 5044-UCD1 is most likely an extreme GC (MV ∼-12.5 mag) belonging to the GC system of the elliptical galaxy NGC 5044.